Molecular Mechanisms and Therapeutic Strategies of Chronic Renal Injury: Role of Rho-Kinase in the Development of Renal Injury - Koichi Hayashi; Shu Wakino; Takeshi Kanda; Koichiro Homma; Naoki Sugano; Takao Saruta (Elsevier, 2006)
Abstract.: Rho/Rho-kinase plays an important role not only in the vasoconstrictor mechanism but also in cellular morphology, motility, adhesion, and proliferation. This pathway also serves to modulate the structure and function of various kidney cells including tubular epithelial cells, mesangial cells, and podocytes. The inhibition of the Rho/Rho-kinase pathway elicits marked increases in renal blood flow in vivo and dilates both afferent and efferent arterioles preconstricted by angiotensin II in vitro. In renal injury, intrarenal angiotensin II is reported to be activated, which subsequently would upregulate the Rho-kinase pathway. A selective Rho-kinase inhibitor, fasudil, has recently been shown to improve renal damage resulting from hypertensive glomerulosclerosis, unilateral ureteral obstruction (for interstitial renal fibrosis) and subtotal nephrectomy. Of interest, fasudil upregulated the expression of p27kip1, a cyclin-dependent kinase inhibitor, and increased the p27kip1 immuno-positive cells in both glomeruli and tubulointerstitium with the use of immunohistochemistry. Collectively, the Rho-kinase pathway is involved in the pathogenesis of renal injury. Clinical application of this type of therapy however awaits further investigations. Keywords:: Rho-kinase, renal hemodynamics, fasudil, renal injury, p27kip1